2014
DOI: 10.1186/1471-2474-15-141
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of employees with arm, neck or shoulder complaints: a focus group study

Abstract: BackgroundMany people suffer from complaints of the arm, neck or shoulder (CANS). CANS causes significant work problems, including absenteeism (sickness absence), presenteeism (decreased work productivity) and, ultimately, job loss. There is a need for intervention programs for people suffering from CANS. Management of symptoms and workload, and improving the workstyle, could be important factors in the strategy to deal with CANS. The objective of this study is to evaluate the experienced problems of employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 38 publications
(54 reference statements)
1
54
1
Order By: Relevance
“…At the workplace, our findings and those of the qualitative studies46 47 combined, suggest addressing physical and cognitive strategies tailored to the individual needs, and using a participatory approach to support commitment from the stakeholders and set priorities 52–55…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…At the workplace, our findings and those of the qualitative studies46 47 combined, suggest addressing physical and cognitive strategies tailored to the individual needs, and using a participatory approach to support commitment from the stakeholders and set priorities 52–55…”
Section: Discussionmentioning
confidence: 77%
“…Two studies may contribute to possible additional factors. One study explored experiences of workers with CANS,46 and reported on the factors: insufficient awareness of possibilities to influence and manage their symptoms, inadequate communication with supervisors and lack of adaptations at the workplace that made it difficult for them to continue working. The other study focused on success factors to continue working in workers with chronic musculoskeletal symptoms 47.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the process of intervention mapping24 25 and based on a recent Dutch multidisciplinary guideline for non-specific CANS,26 and focus group interviews with employees27 and experts,28 we adapted the original programme to suit the needs of employees with CANS, and to alleviate the problems and needs of employees with CANS. The developed intervention included an eHealth module to provide the opportunity to participants to find additional resources which, together with the personal action plans made in the group sessions, would make it possible to tailor the programme to the needs of the individual participant.…”
Section: Introductionmentioning
confidence: 99%
“…physicians jointly determined a classification of patients with non-specific shoulder pain into three subgroups: the first subgroup is patients with pain during abduction (located in the subacromial space), the second one -patients with passive movement limitation (pain of the shoulder joint), and the third one -patients with pain during abduction and passive movement limitation (instability, pain of the acromioclavicular joint or neck) [4]. a tendency for chronic shoulder pain lasting over 6 months has been observed in working people [3]. Half of the patients reporting this problem to their general practitioners manage to recover in half a year, and just 60% -in a year [13].…”
mentioning
confidence: 99%